Fabrication and investigation of physicochemical, food simulant release, and antioxidant properties of whey protein isolate-based films activated by loading with curcumin through the pH-driven method. (November 2020) - Taghavi Kevij, Hossein; Salami, Maryam; Mohammadian, Mehdi; Khodadadi, Maryam
Abstract: In the present study, at first the whey protein isolate (WPI)-curcumin complexes at different concentrations of curcumin including 0, 0.2, 0.5, and 1.0 mg/mL (0, 0.5, 1.25, and 2.5% w/w based on WPI content, respectively) were formed through the pH-driven method to increase the solubility of curcumin. After that, the resulting complexes were employed to produce bioactive edible films and the structural, mechanical, and bio-functional properties of the film samples were also investigated. Fourier-transform infrared spectroscopy showed that the hydrogen bonds were generated between WPI and curcumin in the film matrices. The homogeneous distribution of curcumin in film networks was also confirmed by scanning electron microscopy. The addition of curcumin into the film-forming formulations decreased the average thickness, lightness, water vapor permeability, and elasticity of the films, whereas the redness, yellowness, and strength of complex films considerably increased. The differential scanning calorimetry analysis also suggested a suitable miscibility among the WPI-curcumin complexes. The films enriched with curcumin presented good antioxidant properties as measured by free radical scavenging activity and reducing power assay. Moreover, the results of release test showed that the curcumin released faster and higher from films in 96% ethanol than in 50% ethanol fatty food simulant. Generally, these results suggested that the curcumin-loaded WPI formed by pH-driven method can be used to fabricate bioactive edible antioxidant films. Graphical abstract: Image 1 Highlights: WPI-based bioactive edible films were developed by adding of curcumin. Enriching with curcumin modified the mechanical properties of WPI films. Incorporation of curcumin into WPI film improved its water barrier properties. Enriching with curcumin improved the antioxidant properties of WPI films. Curcumin can be released from films into the fatty and semi-fatty food simulants.